1999
DOI: 10.1046/j.1440-1622.1999.01613.x
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Vocal Fold Paralysis: Causes, Options and Outcomes

Abstract: Early intervention for symptomatic patients was found to be rewarding and safe. Vocal fold augmentation with autologous fat was particularly successful in achieving sustained improvement of voice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 19 publications
3
56
0
3
Order By: Relevance
“…The definitions of ''temporary'' and ''permanent'' vary. For example, Havas et al consider a dysphonia lasting longer than 6 months to be permanent, 11 whereas Wagner and Seiler allow up to 18 months for spontaneous recovery. 12 The majority of studies regard 12 months as being a reasonable spontaneous recovery interval, 13,14 but few studies, if any, provide follow-up data for this length of time.…”
Section: Introductionmentioning
confidence: 99%
“…The definitions of ''temporary'' and ''permanent'' vary. For example, Havas et al consider a dysphonia lasting longer than 6 months to be permanent, 11 whereas Wagner and Seiler allow up to 18 months for spontaneous recovery. 12 The majority of studies regard 12 months as being a reasonable spontaneous recovery interval, 13,14 but few studies, if any, provide follow-up data for this length of time.…”
Section: Introductionmentioning
confidence: 99%
“…The late presentation is due to increased incidence of cancer and cerebovascular accidents among [7] and Glazer [8] who reported the mean age as 53 years. Ahmed et al [9] has also reported maximum number of patients in 5th and 6th decade.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of an obvious cause such as surgical trauma, efforts are required to determine the cause of paralysis since the most common cause is neoplasm. Left vocal fold palsies are more common than those on the right and are much more likely to be due to malignant processes, especially from pulmonary or mediastinal diseases [13][14][15][16]20]. Extensive search for occult causes should be undertaken before diagnosing idiopathic paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of Xth nerve paralysis allows performance of appropriate examinations to determine the underlying cause of paralysis, especially on the skull base, to rule out jugulare foramen abnormalities. However, no distinction is reported in the literature between causes of vocal fold paralysis, either from the recurrent or the Xth nerve [13][14][15][16], and the notion of which appropriate radiologic examinations are required is not addressed.…”
mentioning
confidence: 99%